Genetic Analysis An Integrated Approach - Sanders, Mark Frederick Bowman, John L. (Benjamin Cummings, 2012)
Informed by many years of genetics experience, Mark Sanders and John Bowman use an approach that helps contextualize three core challenges of learning genetics: solving problems, understanding evolution, and understanding the connection between traditional genetics models and more modern approaches.